SNAREing the Basis of Multicellularity: Consequences of Protein Family Expansion during Evolution. - Kloepper, T.H.; Kienle, C.N.; Fasshauer, D. (Molecular Biology and Evolution, 2008)
Vesicle trafficking between intracellular compartments of eukaryotic cells is mediated by conserved protein machineries. In each trafficking step, fusion of the vesicle with the acceptor membrane is driven by a set of distinctive soluble N-ethylmaleimide sensitive factor attachment protein receptor (SNARE) proteins that assemble into tight 4-helix bundle complexes between the fusing membranes. During evolution, about 20 primordial SNARE types were modified independently in different eukaryotic lineages by episodes of duplication and diversification. Here we show that 2 major changes in the SNARE repertoire occurred in the evolution of animals, each reflecting a main overhaul of the endomembrane system. In addition, we found several lineage-specific losses of distinct SNAREs, particularly in nematodes and platyhelminthes. The first major transformation took place during the transition to multicellularity. The primary event that occurred during this transformation was an increase in the numbers of endosomal SNAREs, but the SNARE-related factor lethal giant larvae also emerged. Apparently, enhanced endosomal sorting capabilities were an advantage for early multicellular animals. The second major transformation during the rise of vertebrates resulted in a robust expansion of the secretory set of SNAREs, which may have helped develop a more versatile secretory apparatus.